Predictive impact for postoperative recurrence using the preoperative prognostic nutritional index in pathological stage I non-small cell lung cancer. (August 2016) - Shoji, Fumihiro; Morodomi, Yosuke; Akamine, Takaki; Takamori, Shinkichi; Katsura, Masakazu; Takada, Kazuki; Suzuki, Yuzo; Fujishita, Takatoshi; Okamoto, Tatsuro; Maehara, Yoshihiko
Highlights: PNI is calculated based on serum albumin and lymphocyte count in peripheral blood. We analyzed p-stage I NSCLC patients to investigate effects of preoperative PNI. PNI was an independent prognostic factor in p-stage I NSCLC. The low-PNI group had a significantly shorter RFS, regardless of p-T factors. The preoperative PNI level is a simple and novel predictor of recurrence. Abstract: Background: The most effective treatment for early-stage non-small cell lung cancer (NSCLC) is surgical resection. Nevertheless, up to 20% of patients, even those with stage I NSCLC, relapse after surgery and die. The prognostic nutritional index (PNI) is used to assess immunonutritional conditions or is a predictor of postoperative recurrence in patients with digestive malignancies. However, the usefulness of the PNI for lung cancer is still unknown. We retrospectively analyzed clinicopathological features of stage I NSCLC patients to identify predictors of recurrence and to investigate effects of preoperative PNI levels. Methods: We selected 141 consecutive stage I NSCLC patients who were treated from August 2005 to August 2010. We measured their preoperative PNI levels in uni- and multivariate Cox regression analyses of recurrence-free survival. Results: A low PNI was significantly associated with sex ( P = 0.0117), preoperative serum carcino embryonic antigen levels ( P = 0.0228), and postoperative recurrence ( P < 0.0001). In multivariate analysis, PNI (RR: 9.243; 95% CI: 3.662–25.823; P < 0.0001), pleural invasion (RR: 8.664; 95% CI: 2.510–38.056; P = 0.0005), and intratumoral blood vessel invasion (RR: 3.151; 95% CI: 1.259–7.681; P = 0.0152) were independent prognostic factors. The low-PNI group had a significantly shorter recurrence-free survival than the high-PNI group, regardless of pathological T factors (T1a, P = 0.0422; T1b, P < 0.0001; T2a, P = 0.0098). Conclusions: The preoperative PNI level is a simple and novel predictor of recurrence in stage I NSCLC patients, and might help identify patients who will need multimodality therapy such as induction or adjuvant therapy.